Coronary plaque natural history displays significant longitudinal heterogeneity along the length of individual coronary plaques. (25th November 2020) - Wentzel, J.J; Papafaklis, M; Antoniadis, A; Takahashi, S; Cefalo, N.V; Cormier, M; Saito, S; Coskun, A; Stone, P.H
Abstract: Background: The natural history of plaque growth is, among other systemic risk factors, related to the blood flow induced local shear stress. Especially at regions of low shear stress plaques are initiated. Upon plaque encroachment into the lumen, plaques will be exposed to high shear stress. Interestingly, it has been observed that individual plaques are very heterogeneous regarding the local shear stress exposure and remodeling patterns along the plaque length. However no information is available on the spatial heterogeneity of temporal changes in plaques burden. We studied the longitudinal spatial heterogeneity of plaque burden progression, regression, quiescence in human coronary plaques. Methods: 591 coronary arteries from 302 patients with coronary artery disease who presented with an acute coronary syndrome from the PREDICTION study were investigated for local plaque progression, regression, quiescence patterns after 6–10 months follow up. Arterial geometry was derived from angiography/IVUS-based vascular profiling and reported in 3 mm segments. Plaques were defined as >3 consecutive segments with maximal wall thickness>0.5 mm. Plaque progression was defined as >5% increase, regression as <−5% decrease, and quiescence as no change in plaque burden (plaque area/ total vessel area * 100%). Logistic mixed model regression analysis was performed with plaque progression features as outcome and plaque length as independent variable with vessel as random factor to account for clustering of the data. Results: 5658 3mm-segments of 661 plaques were analyzed. Plaque burden changes over time ranged from −22% to +20%, with an average of −0.4%±4% which was not significant different from 0. Among all plaques, 56% showed segments with plaque progression of more than 5%, 60% with plaque regression (<−5%) and 96% of the plaques had segments that did not change over time (quiescence). On average, 17% of the plaque length displayed plaque progression, 20% regression and 63% was quiescent. The presence and number of features (progression, regression, quiescence) within the plaque were significantly related to the plaque length (figure). Conclusion: Plaques are very heterogeneous in plaque progression patterns. Most of the plaques show within the plaque length simultaneously more than one plaque progression feature (segments that do not change in plaque burden, segments that regress or progress). The number of observed plaque progression features was related to the plaque length. Funding Acknowledgement: Type of funding source: None